Current evidence of temozolomide and bevacizumab in treatment of gliomas - Danop Nanegrungsunk (2018)
© W. S. Maney & Son Ltd 2015. Objective: This review article summarizes in vitro, in vivo, and clinical evidence pertaining to temozolomide (TMZ) and bevacizumab (BEV) efficacy and mechanism of action in gliomas. Methods: Relevant publications published before June 2013 in PubMed database were reviewed. Results: Temozolomide and BEV are current chemotherapeutic agents treating patients with high-grade glioma, including glioblastoma. In vitro and in vivo studies have proposed discordant cell death pathways for TMZ as either apoptosis or autophagy using different experimental setting details or cell lines. In addition, BEV may cause cell death through hypoxia-induced autophagy or unspecific indirect effects on cancer cells. The complexity of cancer cells in glioma has contributed to their resistance of both chemotherapies. In clinical trials, overall survival duration in glioma patients with recurrence (8-9 months) is lower than that in newly diagnosed patients (12-15 months). Conclusion: Our collected data support the addition of radiotherapy, BEV, and other targeted agents to TMZ treatment, indicating prolonged survival duration in newly diagnosed patients. However, the optimal regimen for treating high-grade glioma cannot be concluded without more clinical trials.